LEMBAGA FILANTROPI ISLAM DALAM MENINGKATAN EKONOMI UMMAT - Faizah, Umi (LPPM University 17 Agustus 1945 Samarinda, 2024)
Islamic philanthropy has an important role in community economic empowerment. The conditions of poverty and injustice felt, especially by Muslims, will cause separate and ongoing problems, so it is necessary to make strategic and relevant efforts to unravel the gap in conditions, namely through commendable da'wah activities. That this commendable da'wah is not just to spread religion and call for truth. But da'wah is about how we can see what we can do for our surroundings. This study aims to determine and analyze the potential, role and opportunities of Islamic philanthropy to alleviate poverty and injustice. The results of the study explain that da'wah regarding the problems of poverty and injustice that occur in society need to be unraveled through Islamic da'wah. Islamic philanthropy is a manifestation of our love and care as fellow human beings raising ethical values. The Islamic da'wah agenda through zakat, infaq, shadaqah, and waqaf should be able to unravel domestic problems. With effective activities, well-targeted da'wah, and support from government agencies and institutions, the implementation of Islamic philanthropy provides a solution to the problem of poverty and injustice in Indonesia.